Gender but not nationality matters: acceptance of international and domestic medical student participation in obstetrics and gynecology practice in China based on a cross-sectional study - Bai, Lina; Zhao, Mengmeng; Lu, Chenxi; Tao, Muhan; Gao, Na; Deqiong,; Xiao, Zhen (Frontiers in Education, 2025)
ObjectiveBuilding on our previous study of obstetrics and gynecology outpatients, this study examined inpatients’ acceptance of medical student participation by gender and nationality, and compared findings with outpatient data, attempting to identify potential factors that can balance the patient’s experience and the learning outcomes of medical students.MethodsSelected patients hospitalized in the obstetrics and gynecology wards of a tertiary teaching hospital in China from October 2023 to June 2024 were surveyed and statistically analyzed through the distribution of questionnaires. A total of 750 inpatient questionnaires were distributed, and ultimately 692 usable questionnaires were obtained. Acceptance rates were compared across four groups: Chinese female, Chinese male, international female, and international male medical students. Multivariate analysis identified factors associated with acceptance.ResultsAmong inpatient respondents, acceptance rates for clinical participation by Chinese female, international female, Chinese male, and international male medical students were 71.7%, 70.5%, 51.4%, and 45.7%, respectively. Overall, the acceptance rate is higher than that of outpatients. Regardless of being outpatients or inpatients, the main reason for refusing international medical students is “language barriers.” The analysis shows that physicians sharing more information about the disease is an independent influencing factor affecting inpatients’ acceptance of medical students of all types.ConclusionPromoting the hospital’s teaching role and fostering a sense of altruism, alongside medical students increasing communication with patients, sharing more medical knowledge, and especially international students improving their Chinese language and interpersonal skills, may increase acceptance of medical student participation in obstetrics and gynecology internships by Chinese patients.